Effect of Formulation Variables on Physicochemical Properties of Cholecalciferol Non-aqueous Nanoemulsion - A. Payghan, Dr. Santosh (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The study was to design a stable non-aqueous nanoemulsion (NANE) using cosmetically approved ingredients as a vehicle for the water sensitive active ingredients. Materials and Methods: NANE was designed to increase the dermal penetration and permeation and study solubility and dermal bioavailability of cholecalciferol. For better compliance incorporated the NANEs in cosmetics or personal care products. A non-aqueous system was obtained with glycerin and mineral oil stabilized by glycerol monosterate. It was observed that emulsification behavior is completely unpredictable and conventional theories of emulsification and HLB system cannot be applied here. An optimized non-aqueous cream was obtained through implementation of Box-Behnken experimental design. Cholecalciferol was used as model drug which converts into dehydro cholecalciferol in the presence of water. Result and Discussion: NANE was evaluated by pH, rheology, spreadability, drug content, globule size analysis, zeta potential, and stability. The stability studies (agitation, centrifugation, freeze thaw cycle, accelerated stability) were carried out at 5°C, 25°C and 40°C. Cream was stable at 5°C and 25°C. In vitro drug release shows slow permeation rate but increased retention of cholecalciferol in skin. A comparative study with aqueous formulation shows that non-aqueous cream offers a good stability for cholecalciferol. Conclusion: Results proved that NANE can be used as vehicle for the poorly water-soluble drug, suspension vehicles, and oleogels